The boundaries of international law a feminist analysis, with a new introduction - Charlesworth, Hilary 1955-; Chinkin, Christine 1949- (Manchester University Press, 2022)
In the first book-length treatment of the application of feminist theories of international law, Charlesworth and Chinkin argue that the absence of women in the development of international law has produced a narrow and inadequate jurisprudence that has legitimated the unequal position of women worldwide rather than confronting it. The boundaries of international law provides a feminist perspective on the structure, processes and substance of international law, shedding new light on treaty law, the concept of statehood and the right of self-determination, the role of international institutions and the law of human rights. Concluding with a consideration of whether the inclusion of women in the jurisdiction of international war crimes tribunals represents a significant shift in the boundaries of international law, the book encourages a dramatic rethinking of the discipline of international law. With a new introduction that reflects on the profound changes in international law since the book's first publication in 2000, this provocative volume is essential reading for scholars, practitioners and students alike.
Previous edition: 2000
Literaturverzeichnis: Seite 338-378, Register
Keywords: Feministische Rechtswissenschaft; Internationales Recht; International law; Feminist jurisprudence; Women / Legal status, laws, etc